House dust microbiome differentiation and phage-mediated antibiotic resistance and virulence dissemination in the presence of endocrine-disrupting chemicals and pharmaceuticals - Shicong Du; Huiju Lin; Qiong Luo; Chung Ling Man; Sze Han Lai; Kin Fai Ho; Kenneth M. Y. Leung; Patrick K. H. Lee (Microbiome)
Abstract Background House dust serves as a reservoir of a diverse array of microbial life and anthropogenic chemicals, both of which can potentially influence the health of occupants, particularly those who spend significant amounts of time at home. However, the effects of anthropogenic chemicals on dust microbiomes remain poorly understood. This study investigated the presence of anthropogenic chemicals in the dust of homes occupied by elderly occupants and explored those chemicals’ relationships with dust microbiomes. Results We detected 69 out of 76 analyzed anthropogenic chemicals, including endocrine-disrupting chemicals, non-antibiotic pharmaceuticals, and antibiotics, in at least one house dust sample from 32 residential homes, with concentrations ranging from 2720 to 89,300 ng/g. Some of these detected compounds were pharmaceuticals regularly consumed by the occupants. The dust microbiomes were associated with varying levels of anthropogenic chemicals, forming two distinct clusters, each with unique diversity, taxonomy, metabolic functions, and resistome profiles. Higher concentrations and a greater variety of these chemicals were associated with an increased co-occurrence of antibiotic resistance and virulence genes, as well as an enhanced potential for their transfer through mobile genetic elements. Under these conditions, phages, especially phage-plasmids, facilitated the dissemination of antibiotic resistance and virulence among bacterial populations. Conclusions The findings indicate that everyday anthropogenic chemicals are important factors associated with the microbes in indoor environments. This underscores the importance of improving household chemical stewardship to reduce the health risks associated with exposure to these chemicals and their effects on indoor microbiomes. Video Abstract